2020
DOI: 10.1111/1745-9133.12509
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year outcomes following naloxone administration by police officers or emergency medical services personnel

Abstract: We conducted a retrospective, quasi-experimental study of a police naloxone program to examine individual outcomes following nonfatal overdose where either police (n = 111) or emergency medical services (n = 1,229) provided a first response and administered naloxone. Individuals who received a police response were more likely to be arrested immediately following initial dispatch and had more instances of repeat nonfatal overdose two years following dispatch; there were no differences in rearrest or death rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Our finding that officers force overdose victims to go to jail if they do not consent to be transported to hospitals corroborates other studies (e.g., Carroll et al,2020;Lowder et al,2020). Carroll and colleagues' study showed that over one-third of surveyed officers who had administered naloxone reported arresting someone following an overdose reversal (2020) and communitybased studies of people who use drugs have also found that overdose victims are often taken to jail (e.g., Park et al,2019;Wagner et al,2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that officers force overdose victims to go to jail if they do not consent to be transported to hospitals corroborates other studies (e.g., Carroll et al,2020;Lowder et al,2020). Carroll and colleagues' study showed that over one-third of surveyed officers who had administered naloxone reported arresting someone following an overdose reversal (2020) and communitybased studies of people who use drugs have also found that overdose victims are often taken to jail (e.g., Park et al,2019;Wagner et al,2019).…”
Section: Discussionsupporting
confidence: 89%
“…Although officers have been found to be aware of their state's GSL (Banta-Green et al,2013;Carroll et al,2020;Saucier et al,2016;Wagner et al,2016), research has shown that overdose calls for service can result in arrests (Lowder et al,2020) for crimes including public intoxication, possession of drug paraphernalia, or outstanding warrants (Deonarine et al,2016). Carroll et al's (2020) sample of 2829 officers in 20 states found that 37% had reported administering naloxone at least once in the past 6 months and 36% reported having made at least one arrest at an overdose scene.…”
Section: Introductionmentioning
confidence: 99%
“…might need other types of help. Similarly, Lowder et al (2020) argue this can occur when giving officers naloxone to respond to opioid overdoses (as oppose to letting medical responders handle overdoses).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…There is preliminary evidence showing those with a non-fatal overdose are more likely to have been arrested for drug possession within 6 months of their overdose [ 15 ]. Another study examining outcomes following a police response to a non-fatal overdose requiring naloxone administration found that, compared to an emergency medical services (EMS) response, a police response was more likely to result in arrest immediately following the overdose response [ 16 ]. While that study did not find differences in recidivism or mortality rates over two-year follow-up among the groups who received an overdose response from the police versus EMS, it excluded responses when both police and EMS participated (which is a common scenario) and did not focus on pre–post-assessment of outcomes within each group.…”
Section: Introductionmentioning
confidence: 99%